Antioxidant properties and mineral composition of saba banana [Musa acuminata x balbisiana (ABB Group)] peel tea - Favila, Noelle Alexys M.
More than a million metric tons of waste in the form of peels are generated annually from the production and consumption of bananas which are a major crop and snack in the Philippines. This is despite the potential of the peel for various uses, including food use, especially since it contains significant amounts of nutrients and phytochemicals that exceed those in the pulp. There is also a lack of literature on banana peels, particularly from bananas at the unripe stage of maturity and as a raw material for herbal tea. This study addresses this gap by assessing the beneficial bioactive compounds of tea prepared from peels of unripe and ripe Saba bananas at different decocting periods (10, 20, 30 minutes) in terms of antioxidant properties and mineral composition. The peels were sourced mostly from small businesses that regularly utilize Saba bananas and do not have any more use for them, and were brewed into tea in a 1:8 ratio with water. Results from laboratory and statistical analyses show that antioxidant properties significantly increase in mean value (p < 0.001) at the ripe stage of maturity, and mineral contents significantly increase in mean value (p < 0.001) both at the ripe stage of maturity and with longer decocting periods. Consequently, tea samples prepared from peels of ripe Saba bananas at a decocting period of 30 minutes had the highest values for antioxidant properties and mineral contents. This study was able to utilize peels from unripe and ripe Saba bananas, which would have been wasted, and prove the presence of bioactive compounds in them that can be beneficial to human health.